Contribution of Sharia Supervisory Board (SB) and Sharia Compliance Levels to Performance Indonesian Sharia Banking - Ningsih, Prilla Kurnia (Jurnal Manajemen, 2020)
Sharia compliance is an absolute requirement that must be fulfilled by financial institutions that conduct business activities based on sharia principles as a manifestation of the characteristics of Islamic financial institutions. Supervisory Board (SB) contribution oversees and is responsible for ensuring all products and procedures of Islamic banks are by sharia principles. This study aims to measure the ratio of participation, effectiveness and efficiency of the sharia supervisory board to Islamic banking in Indonesia. This study used the AHP method with three indicators; the rate of contributions measured through sharia branch office in public Islamic bank and sharia business unit, to the effectiveness ratio measured by the total productive assets variable in public Islamic and sharia businesses unit, while the efficiency ratio is measured by aggregate variables of operating expenses and labour costs for Islamic public bank and sharia businesses unit. Based on this research, here are some critical result such as the ratio of the overall contribution is useful. The effectiveness ratio shows that the Supervisory Board (SB) is ineffective or not valuable for lending activities in Islamic banks based on Islamic public bank branch offices and sharia businesses unit. And the results for efficiency ratios indicate that overall Supervisory Board (SB) is less efficient for Islamic banks when issuing operational costs on Supervisory Board (SB) contributions.